Digital Native Experience: Learning English beyond Classroom - Vera Nursyarah; Nur Arifah Drajati; Ngadiso Ngadiso (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Extensive listening is an enjoying and meaningful listening activity which is be able to apply both in class and out of classroom. This study was to delve deeper understanding into how English student-teachers use their self-motivating strategy while using Extensive Listening in order to keep themselves motivated when facing various kinds of situation which affect their learning process. It is necessary to keep them motivated to learn independently by using various resources available on the internet such as YouTube, BBC learning English, or TED Ed to shape their habit in English listening development. Multiple participants were chosen in the study. There were 4 students of English education from one of the state University in Indonesia who are used to do Extensive Listening activity. The data were obtained from participants' autobiographies, interviews, and learners’ diary. The experience of EFL students in practicing Extensive Listening was told by the participants through their learning journals and interview. This study showed that most participants use environmental control strategies to avoid disturbances from the environment, satiation control to eliminate boredom, and metacognitive control to manage their focus and concentration. Meanwhile, emotional control was not used by participants. Some of participants will try to use commitment control strategy in the future. Therefore, this study indicated that English teachers or lecturers must be aware that self-regulation skills which is used by students outside the classroom is able to support students’ listening development in the foreign language English classroom.